Ag3PO4-anchored La2Ti2O7 nanorod as a Z-Scheme heterostructure composite with boosted photogenerated carrier separation and enhanced photocatalytic performance under natural sunlight. (15th April 2023) - Chen, Xiaojuan; Chen, Jieming; Li, Ning; Li, Jiesen; He, Juhua; Xu, Song; Zhu, Yanping; Yao, Liang; Lai, Yiqi; Zhu, Runliang
Abstract: Developing wide spectra-responsive photocatalysts has attracted considerable attention in the photocatalytic technology to achieve excellent catalytic activity. Ag3 PO4, with strong response to light spectra shorter than 530 nm, shows extremely outstanding photocatalytic oxidation ability. Unfortunately, the photocorrosion of Ag3 PO4 is still the biggest obstacle to its application. Herein, the La2 Ti2 O7 nanorod was used to anchor Ag3 PO4 nanoparticles in this study, and a novel Z-Scheme La2 Ti2 O7 /Ag3 PO4 heterostructure composite was constructed. Remarkably, the composite showed strong responsive to most of the spectra in natural sunlight. The Ag 0 formed in-situ acted as the recombination center of photogenerated carriers, which promoted their efficient separation and contributed to the improved photocatalytic performance of the heterostructure. When the mass ratio of Ag3 PO4 in the La2 Ti2 O7 /Ag3 PO4 catalyst was 50%, the degradation rate constant of Rhodamine B (RhB), methyl orange (MO), chloroquine phosphate (CQ), tetracycline (TC), and phenol under natural sunlight irradiation were 0.5923, 0.4463, 0.1399, 0.0493, and 0.0096 min −1, respectively. Furthermore, the photocorrosion of the composite was greatly inhibited, 76.49% of CQ and 83.96% of RhB were still degraded after four cycles. Besides, the holes and O2 − played a significant role in RhB degradation, and it included multiple mechanisms of deethylation, deamination, decarboxylation, and cleavage of ring-structures. Moreover, the treated solution can also show safety to the water receiving environment. Overall, the synthesized Z-Scheme La2 Ti2 O7 /Ag3 PO4 composite exhibited immense potential for removing various organic pollutants through photocatalytic technology under natural sunlight irradiation. Graphical abstract: Image 1 Highlights: Ag3 PO4 -anchored La2 Ti2 O7 nanorod as a Z-Scheme heterostructure composite was constructed. La2 Ti2 O7 /Ag3 PO4 showed excellent photocatalytic activity under natural sunlight. The photocatalytic system behaved good applicability to various factors. Photocatalytic stability of La2 Ti2 O7 /Ag3 PO4 was greatly enhanced. Biological toxicity of degradation solution was reduced.